Collective situations readings in contemporary Latin American art 1995-2010 - Kelley, Bill 1970-; Kester, Grant H. (Duke University Press, 2017)
Introduction / Grant Kester and Bill Kelley Jr. -- (Un)civil disobedience -- Lava la bandera : the Colectivo Sociedad Civil and the cultural overthrow of the Fujimori-Montesinos dictatorship / Gustavo Buntinx -- Interview with Caleb Duarte of Edelo Residencia / Raquel de Anda -- Grupo Etcétera : project description / Rodrigo Martí -- An interview with Etcétera / Etcétera -- Artistas en Resistencia : project description / Kency Cornejo -- An interview with Artistas en Resistencia / Kency Cornejo -- A long way : Argentine artistic activism of the last decades / Ana Longoni -- Urbanism -- Galatea/bulbo collective : project description / Mariola V. Alvarez -- Interview with Tranvía Cero / María Fernanda Cartagena -- Art collectives and the Prestes Maia occupation in São Paulo / Gavin Adams -- Frente 3 de fevereiro : project description / Rodrigo Martí -- Interview with Mauricio Brandão of Bijari, october 9, 2011 / Mariola V. Alvarez -- Memory --
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte 1995-2010; Art, Latin American / 21st century; Art, Latin American / 20th century; Group work in art / Latin America; Kunst; Künstlervereinigung; Lateinamerika; Aufsatzsammlung